Rachel Carson’s Silent Spring: A Plea for Changing Environmental Policy - Ravindra Neupane; Vasily V. Verkhoturov (RUDN Journal of Studies in Literature and Journalism)
Analyzes how Rachel Carson’s 1962 book Silent Spring significantly influenced the Change in Environmental Policy. Historically, when academics talk about attempts to change environmental policy, they primarily focus on the contributions of natural and social scientists who assess the effects of pollution and other harmful factors on the environmental response to the increased use of pesticides in the 1960s, Carson produced her cross-disciplinary book, which combined environmental science and narrative. Silent Spring was able to influence and start changes in the laws governing chemical insect control and the outlawing of the synthetic pesticide DDT (dichloro-diphenyl-trichloroethane). By challenging the conventional wisdom that viewed man as the master and master of nature, Carson’s book changed policy and inspired new research, demonstrating that the overuse of pesticides is both dangerous and immoral. Her book is considered a founding work of the contemporary environmental movement. The links between science, literature, and public participation that have the potential to increase public understanding of the significance of environmental literature as a tool for influencing environmental policy is the issue this paper has explored in the novel. Applying qualitative research design, this article critically examines and analyzes the environment from a crossdisciplinary approach, using Silent Spring as an exemplary case of a literary text that can affect environmental policy, both in the academic and, more crucially, in real life. Lawrence Buell’s critical insights on the environmental realities that the text portrays serve as a theoretical perspective to analyze the novel.